2015
DOI: 10.1523/jneurosci.4595-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Network Anisotropy Trumps Noise for Efficient Object Coding in Macaque Inferior Temporal Cortex

Abstract: How neuronal ensembles compute information is actively studied in early visual cortex. Much less is known about how local ensembles function in inferior temporal (IT) cortex, the last stage of the ventral visual pathway that supports visual recognition. Previous reports suggested that nearby neurons carry information mostly independently, supporting efficient processing (Barlow, 1961). However, others postulate that noise covariation effects may depend on network anisotropy/homogeneity and on how the covariati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The second motivation was the need of excluding potential effects of top-down signals, task- and state-dependence, learning and memory ( Gavornik and Bear, 2014 ; Cooke and Bear, 2015 ; Burgess et al, 2016 ), which are all detrimental when the goal is to understand the initial, largely reflexive, feed-forward sweep of activation through a visual processing hierarchy ( DiCarlo et al, 2012 ). For these reasons, many primate studies have investigated ventral stream functions in anesthetized monkeys [e.g., see ( Kobatake and Tanaka, 1994 ; Ito et al, 1995 ; Logothetis et al, 1999 ; Tsunoda et al, 2001 ; Sato et al, 2013 ; Chen et al, 2015 )] or, if awake animals were used, under passive viewing conditions [e.g., see ( Pasupathy and Connor, 2002 ; Brincat and Connor, 2004 ; Hung et al, 2005 ; Kiani et al, 2007 ; Willmore et al, 2010 ; Rust and Dicarlo, 2010 ; Hong et al, 2016 ; El-Shamayleh and Pasupathy, 2016 )].…”
Section: Discussionmentioning
confidence: 99%
“…The second motivation was the need of excluding potential effects of top-down signals, task- and state-dependence, learning and memory ( Gavornik and Bear, 2014 ; Cooke and Bear, 2015 ; Burgess et al, 2016 ), which are all detrimental when the goal is to understand the initial, largely reflexive, feed-forward sweep of activation through a visual processing hierarchy ( DiCarlo et al, 2012 ). For these reasons, many primate studies have investigated ventral stream functions in anesthetized monkeys [e.g., see ( Kobatake and Tanaka, 1994 ; Ito et al, 1995 ; Logothetis et al, 1999 ; Tsunoda et al, 2001 ; Sato et al, 2013 ; Chen et al, 2015 )] or, if awake animals were used, under passive viewing conditions [e.g., see ( Pasupathy and Connor, 2002 ; Brincat and Connor, 2004 ; Hung et al, 2005 ; Kiani et al, 2007 ; Willmore et al, 2010 ; Rust and Dicarlo, 2010 ; Hong et al, 2016 ; El-Shamayleh and Pasupathy, 2016 )].…”
Section: Discussionmentioning
confidence: 99%
“…Given that we did not measure the response covariance matrix and are ignorant about its readout, we cannot make claims about how well (i.e., quantitatively) the brain can decode the IT population responses. Chen, Lin, Hsu, & Hung (2015) assessed the effect of noise correlation in a small population of IT neurons (up to 87 neurons) on object decoding with a linear classifier. They found that noise correlations slightly decreased decoding, which is in line with their on average positive signal correlations.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring correlations alone does not show whether they impact information coding, because it is the relation between average population activity and the structure of the noise correlations that affects information. Noise correlations have been shown to increase (Romo et al, 2003;Zavitz et al, 2019), decrease (Chen et al, 2015;Graf and Andersen, 2015), or have minimal effect (Averbeck andLee, 2003, 2006; on information coding. Across these studies, measured effects have been modest, and they were estimated in small ensembles of at most 10 s of neurons.…”
Section: Introductionmentioning
confidence: 99%